Empirical vs. Evidence-Based: Evaluating the Alignment of Initial Antibiotic Therapy with Local Antibiogram Data - Rasool Chaloob Hulyal (Academia Open, 2026)
General Background: Antimicrobial resistance represents a major global health challenge requiring alignment of empiric antibiotic therapy with local susceptibility data. Specific Background: In clinical practice, variability persists between empiric prescribing and antibiogram-based expectations despite stewardship recommendations. Knowledge Gap: Real-world evidence on the degree of concordance and its association with clinical outcomes in hospital settings remains limited. Aims: This study evaluated concordance between initial empiric antibiotic therapy and local antibiogram data and examined outcomes associated with discordant therapy. Results: Among 512 patients, overall concordance was 64.8%, while 35.2% received discordant therapy. Concordance was highest in urinary tract infections (76.2%) and lowest in pneumonia (52.9%), and was reduced in intensive care settings (54.8%) compared with medical wards (71.3%). Gram-negative pathogens predominated, with Escherichia coli (37.7%) and Klebsiella pneumoniae (22.5%) most frequent. Independent predictors of resistance included prior antibiotic exposure, hospital-acquired infection, and intensive care admission. Discordant therapy was associated with longer hospitalization (11 vs 7 days) and higher antibiotic escalation rates (46% vs 18%), with a non-significant increase in mortality. Novelty: This study integrates antibiogram concordance analysis with clinical outcomes and identifies healthcare-associated predictors within a single cohort. Implications: Strengthening integration of local antibiograms into empiric prescribing pathways may support optimized antibiotic use and address antimicrobial resistance. Highlights:• One-Third of Initial Treatments Did Not Match Susceptibility Expectations.• Critical Care and Respiratory Cases Showed Lowest Alignment Rates.• Mismatch Linked to Longer Stays and Higher Treatment Escalation. Keywords: Antimicrobial Resistance, Empiric Antibiotic Therapy, Antibiogram, Antimicrobial Stewardship, Clinical Outcomes.